Analisa Peran Proses Block Control (PBC) terhadap Sistem Operasi pada Windows 10 - Fadhila Ramadhani; Muhammad Firdaus (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
In today’s era, we are very familiar with operating systems that function to manage the work of hardware and software so they can be used properly. One of the most widely used operating systems is Windows, because it has an easy-to-understand interface and is capable of running multiple applications simultaneously. To support this, Windows requires a process management mechanism, namely a way for the system to organize running programs so they do not interfere with each other and remain stable. In process management, there is an important component called the Process Control Block (PCB). The PCB can be likened to an identity card or a complete record of a process, as it contains information such as the process ID, status, CPU usage, memory, and files being used. This study aims to analyze the role of the process control block, focusing on how the Process Control Block stores important information regarding the status and activity of each process, ensuring smooth, efficient, and non-conflicting application execution. In this research, experiments were conducted to measure CPU usage, memory, and execution time by various processes with different priorities to observe the information of running processes. The analysis results show that each application has its own Process ID and PCB, which records status, CPU registers, memory allocation, and I/O resources used. The PCB enables multiple applications to perform multitasking effectively.